Pengaruh Corporate Governance dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan Sub Sektor Perbankan Yang Terdaftar Di BEI - Lisna, Lisna; Hasbuddin, Hasbuddin; Asni, Nur (Universitas 17 Agustus 1945 Jakarta, 2025)
This study intends to empirically analyze the influence of corporate governance and firm size on financial performance. T This study utilizes quantitative data obtained from annual reports and financial statements of banking companies. The population includes all banking sub-sector firms listed on the Indonesia Stock Exchange during 2019–2023. Samples were selected through purposive sampling, so that 43 companies were selected as the research objects. Data analysis was performed using panel data regression with EViews 12 software. The findings indicate that corporate governance, measured by the presence of independent commissioners, significantly affects financial performance, while the board of directors and audit committee show no significant effect. Furthermore, firm size is proven to have a significant impact on financial performance. Simultaneously, corporate governance and firm size also influence financial outcomes. Therefore, companies are advised to strengthen the implementation of good corporate governance principles and enhance assets to improve financial performance.